Information technology in Philippine libraries an analysis using the Hegelian Dialectic - Ileto, Dina I. (School of Library and Information Studies, University of the Philippines Diliman, 2016)
This research determined the evolution of the library and its dichotomy with technology and identified progress of change in the library, librarianship and library services in the country. By attaining the objectives of this study, the current state of the libraries in the Philippines was determined and by applying the dialectics of Hegel (thesis, antithesis and synthesis), the Philippine libraries' different turning points were identified. Finally, the research examined these turning points and their importance to the study of Information and Library Science. This study referred to and reviewed qualitative research from electronic databases and published works.